2010
DOI: 10.1002/cncr.25074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of classification systems in melanoma sentinel lymph nodes—An analysis of 697 patients from a single center

Abstract: BACKGROUND:In melanoma, different classification systems have been proposed that predict overall survival (OS) and recurrence-free survival (RFS) based on findings in the sentinel lymph node (SLN). The authors of this report compared the RFS and OS of 697 melanoma patients as predicted by various classification systems. METHODS: The Rotterdam system (based on the greatest dimension of the largest tumor cell deposit), the Augsburg S-classification (based on tumor penetrative depth [TPD]), and the Hannover syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
2
33
1
14
Order By: Relevance
“…Roka et al [8] reported an SLN tumour size >2 mm, presence of NSLN involvement and Breslow thickness to be associated with different recurrence-free and disease-specific survival and confirmed the prognostic relevance of the S/U score proposed by Reeves et al [20] In another paper, the presence of micro-metastatic tumour deposits in SLN was associated to a significantly better prognosis with respect to macrometastases [9]. A recent German study [39] found the greatest dimension of the largest tumour cell deposit, the tumour penetrative depth and capsular involvement as independent parameters for relapsefree and overall survival. The invasion depth (Starz classification) [17] was also found by previous studies to best predict overall survival [16], [18] and [40].…”
Section: Discussionmentioning
confidence: 72%
“…Roka et al [8] reported an SLN tumour size >2 mm, presence of NSLN involvement and Breslow thickness to be associated with different recurrence-free and disease-specific survival and confirmed the prognostic relevance of the S/U score proposed by Reeves et al [20] In another paper, the presence of micro-metastatic tumour deposits in SLN was associated to a significantly better prognosis with respect to macrometastases [9]. A recent German study [39] found the greatest dimension of the largest tumour cell deposit, the tumour penetrative depth and capsular involvement as independent parameters for relapsefree and overall survival. The invasion depth (Starz classification) [17] was also found by previous studies to best predict overall survival [16], [18] and [40].…”
Section: Discussionmentioning
confidence: 72%
“…In a comparative study, two protocols (lamination and halving according to EORTC recommendations) were equivalent in detecting melanoma metastases in the sentinel lymph node [189]. Using these protocols, various studies have shown 25-30 % of melanoma patients with a primary tumor > 1 mm to be positive [189][190][191][192][193][194][195][196].…”
Section: R Gutzmermentioning
confidence: 99%
“…However, some parameters are looming, which have prognostic relevance or may be able to predict involvement of further, non-sentinel lymph nodes in the affected basin. In particular, they include length of the largest melanoma cell cluster [193,196,204,205], maximum depth of melanoma cell penetration from the lymph node capsule into the lymph node parenchyma [191,193,195], infiltration of the lymph node capsule [190,193], lymphangiosis, i.e. accumulation of tumor cells within lymph vessels outside the sentinel lymph node [204][205][206], and location of melanoma cells inside the lymph node, e.g.…”
Section: R Gutzmermentioning
confidence: 99%
See 2 more Smart Citations